A single-atom detector integrated on an atom chip: fabrication, characterization and application - Heine, Dennis; Rohringer, W.; Fischer, D.; Wilzbach, Marco; Raub, T.; Loziczky, S.; Liu, XiYuan; Groth, S.; Hessmo, Björn; Schmiedmayer, Hannes-Jörg (New journal of physics, 2010)
We describe a robust and reliable fluorescence detector for single atoms that is fully integrated on an atom chip. The detector allows spectrally and spatially selective detection of atoms, reaching a single-atom detection efficiency of 66%. It consists of a tapered lensed single-mode fiber for precise delivery of excitation light and a multi-mode fiber to collect the fluorescence. The fibers are mounted in lithographically defined holding structures on the atom chip. Neutral 87Rb atoms propagating freely in a magnetic guide are detected and the noise of their fluorescence emission is analyzed. The variance of the photon distribution allows us to determine the number of detected photons per atom and from there the atom detection efficiency. The second-order intensity correlation function of the fluorescence shows near-perfect photon anti-bunching and signs of damped Rabi oscillations. With simple improvements, one can increase the detection efficiency to 95%.